Comparative Analysis of Student Preferences for the Use of Online Learning Media: Same or Different? - Ningsih, Yuni Setia (MANDAILING GLOBAL EDUKASIA, 2024)
UIN Ar-Raniry students came from various educational backgrounds, such as senior high school, vocational school, islamic high school, and islamic boarding school. Students from the 2024/2025 academic year are part of a generation that is familiar with technology. They have their own preferences in responding to the use of online learning media. This research aims to analyze student preferences for learning classes and learning resources associated with online learning media. Data was obtained by administering a Likert scale questionnaire via Google Form. Based on research data, it is known that even though they are used to technology, they do not consider online learning media as a necessity. Their attitudes towards online learning media tend to be good or neutral, with a balanced preference between using online and offline learning media. In general, the preferences of students from various educational backgrounds show similarities in the use of online learning media, without any significant differences based on their educational backgrounds.